PERBAIKAN PERTUMBUHAN BIBIT JATI LOKAL MUNA (Tectona grandis Linn. F) ASAL BENIH MELALUI PERBANDINGAN KOMPOSISI MEDIA DAN BERBAGAI JENIS KOMPOS - Sulyanti Sanusi; Saida Saida; Suriyanti Suriyanti (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
This study aims to determine the effect of the comparison of media composition on the growth of teak seedlings; knowing the response of the growth of teak seedlings to the use of various types of compost; and knowing the interaction between media composition and the use of various types of compost on the growth of teak seedlings.This study used a factorial randomized block design consisting of two factors, namely the media composition factor which consisted of 3 levels, namely 1: 2, 2 : 1, 1: 1 and factor B (type of compost) which consisted of 3 types, namely tricocompost, bokashi and vermicompost and repeated 3 times and each replication consisted of 5 plants. The study was conducted from July to December 2019. The data obtained were analyzed by Analysis of Variety. If there is a significant difference, it is continued with the Tukey Test. The variables observed in the study were the increase in plant height; increase in stem diameter; number of leaves; Seedling Robustness Value (NKS) and Seed Quality Index (IMB).The results showed that the best treatment interaction for increasing diameter was the type of bokashi with a ratio of 1: 1, the increase in diameter of the type of bokashi in a ratio of 1: 2, the type of compost in the parameter of the number of leaves of the Tricokompos type in a ratio of 2: 1, the Sturdy Value of Seedlings (NKS) of the Tricokompos type with a ratio of 2 : 1 and the Quality Index of Tricocompost type seeds with a ratio of 1: 2.